RS3PE as Paraneoplastic Rheumatic Syndrome: A Brief Overview and Review of Case Series - Firsty, Naufal Nandita (SCRIPTA SCORE Scientific Medical Journal, 2021)
Background: RS3PE stands for remitting seronegative symmetrical synovitis with pitting edema thus described in some literature worldwide as a group of symptoms or a syndrome and first described by McCarty in 1985. RS3PE is also known as a rare form of rheumatology pathologic condition correlates with inflammatory arthritis. In past years, the diagnosis of RS3PE should raise the clinician suspicion of the more aggressive possibility of underlying malignancy. Rheumatology and malignancy can share some of its symptoms in various ways, especially in the musculoskeletal system as the main rheumatology focus. Methods: Literature review is the used method that focused on publication between January 2011 to 2020 to keep up with the current medical science, which is done using certain keywords. Discussion: There is a plethora of literature describing paraneoplastic syndrome and its relation with underlying malignancy, especially prostate and lung adenocarcinoma. RS3PE itself is closely related to VEGF either its idiopathic form or paraneoplastic form; thus, the clinical feature appears similar. In terms of malignancies, VEGF acts as a key role in its pathology as an important growth factor because of VEGF nature as a potent angiogenic molecule. In some malignancies, the VEGF level also appears to be higher than normal, thus suggesting an explanation of paraneoplastic syndromeâ€™s nature. Conclusion: RS3PE has been strongly correlated with several malignancies mostly prostate cancer; thus should raise the awareness of clinician its signs and symptoms exist in a ce1rtain risky group even if the â€œpureâ€ form of RS3PE exists. Keywords: malignancy, paraneoplastic syndrome, rheumatology, RS3PE Â  Latar Belakang: RS3PE merupakan singkatan dari remitting seronegative symmetrical synovitis with pitting edema sehingga dideskripsikan pada berbagai literatur di seluruh dunia sebagai kumpulan gejala atau sindroma yang pertama kali disebutkan oleh McCarty pada tahun 1985. RS3PE juga diketahui sebagai bentuk kondisi reumatologi patologis yang berkorelasi dengan artritis inflamatorik. Beberapa tahun terakhir, diagnosis dari RS3PE harus meningkatkan kecurigaan seorang praktisi kesehatan terhadap keganasan yang melatarbelakangi. Reumatologi dan keganasan juga memiliki beberapa kesamaan perihal gejala dalam bentuk yang berbeda-beda terlebih pada sistem muskuloskeletal sebagai fokus utama reumatologi. Metode: Tinjauan pustaka merupakan metode yang digunakan dan berfokus pada publikasi pada rentang waktu Januari 2011 hingga Desember 2020 sehingga penulisan manuskrip ini masih berdasarkan pengetahuan medis yang terbarukan dan dilakukan menggunakan beberapa kata kunci. Pembahasan: Cukup banyak manuskrip yang telah diterbitkan untuk mendeskripsikan sindroma paraneoplastik dan korelasinya terhadap suatu keganasan. RS3PE, sebagai suatu sindroma paraneoplastik telah dilaporkan oleh berbagai praktisi kesehatan seluruh dunia mengenai korelasinya tehadap beberapa patologi keganasan terutama pada organ prostat, paru, dan kolorektal. RS3PE sendiri erat dikaitkan dengan VEGF baik bentuk idiopatiknya ataupun bentuk paraneoplastiknya. Perihal keganasan, VEGF memiliki peranan yang cukup vital dalam patologinya terkhusus pada faktor pertumbuhan oleh karena sifat dari VEGF sebagai molekul angiogenik potensial. Pada beberapa keganasan, nilai VEGF ditemukan lebih tinggi daripada populasi normal sehingga diduga, menjelaskan penyebab dari suatu kejadian sindroma paraneoplastic. Kesimpulan: RS3PE telah dikorelasikan dengan erat terhadap beberapa keganasan terutama kanker prostat dan kanker kolorektal dengan jumlah yang lebih sedikit sebagai etiologi dari RS3PE sebagai suatu sindroma paraneoplastik walaupun bentuk idiopatiknya ada. Kata Kunci: keganasan, reumatologi, RS3PE, sindroma paraneoplastik